Bobot karkas dan persentase potongan karkas itik petelur mojosari yang diberi pakan dengan suplementasi kalsium fitobiotik: Weight and percentage of carcass of mojosari laying duck pieces with calcium phytobiotics in the diet - Cindy A. Damayanti; Muhammad Andika Yudha Harahap; Adam E. Saputra; Syahputra Wibowo; Irfan H. Djunaidi; Osfar Sjofjan (Fakultas Peternakan Universitas Papua, 2023)
Feed additives is important to improve the appearance of duck production. The purpose of this study was to determine the weight and proportion of Mojosari Laying Duck carcass parts that contained calcium phytobiotics. Twenty-four flocks of 120 mojosari laying ducks (24-week-old) were used. Variation Analysis was used to statistically examine the data (ANOVA). Duncan's Multiple Distance Test is used if the study's data show a substantial difference between treatments. A Complete Randomized Design is employed using 6 treatments and 4 tests, each containing 5 mojosari laying ducks. Treatment (P0) is the control feed, (P1) is the control feed plus zinc bacitracin, (P2) is the control feed plus phytobiotics 0.25%, (P3) is the control feed plus phytobiotics 0.50%, (P4) is the control feed plus phytobiotics 0.75%, and (P5) is the control feed plus 1% phytobiotics. The findings demonstrated that the addition of phytobiotic calcium did not significantly affect carcass weight or the percentage of carcass parts (P>0.05). However, (P2) increased the carcass weight compared to the control meal. Weight of the carcass produced is 792.50±91.06 – 972.50±86.84. The percentage of carcasses is 50±0.05 - 57±0.07. The percentage of back pieces was 32.19±1.54 – 36.32±2.94. The percentage of chest pieces was 7.26±0.84 – 8.63±0.97. The percentage of wing pieces was 14.46±0.48 – 13.63±1.93. The percentage of upper thigh pieces produced was 9.50±0.82 – 10.35±2.31, and the percentage of lower thigh pieces was 11.48±0.91 – 13.34±1.97. Results showed that the addition of phytobiotic calcium did not significantly affect the proportion of parts and carcass weight (P>0.05).